Crafting happiness from everyday life: Personality, personal projects, basic psychological need satisfaction, and well-being - Taylor G. Hill; Emma C. Coughlan; Sean P. Mackinnon (International Journal of Personality Psychology, 2023)
Introduction: Feeling competent, related, and autonomous promotes well-being through satisfying basic psychological needs, according to self-determination theory’s basic psychological need satisfaction mini-theory. Personal projects are personally relevant goal-directed activities that take place over an extended period. The quality of life elicited from pursuing personal projects depends on the degree to which projects provide a sense of relatedness, competence, and autonomy. We expected that, when controlling for perfectionistic standards and discrepancies, achievement striving would lead to the pursual of projects that provide a sense of competence, which in turn leads to well-being. We also explored autonomy and relatedness as mediators. Methods: The sample (N = 327) was composed of students and the general adult population who provided information on positive mental health, passion, zest for life, life purpose, personality, basic psychological need satisfaction, and personal projects. We used a cross-sectional survey design and tested hypotheses with twelve serial mediation models. Results: Achievement striving and personal standards were positively associated with competence, which in turn predicted well-being in 12 of 12 indirect effects tested. Achievement striving, personal standards and discrepancies contributed to change in well-being through relatedness or autonomy in 9 of 24 of exploratory indirect effects tested. Discussion: Those oriented toward achievement motivation are likely to feel competent in their pursuits (personal projects), which in turn promotes well-being. Pursuing personal projects that suit one’s personality (i.e., make it more likely to meet basic psychological needs) may be a tool to boost well-being.